Leadership Character According To Imam Al-Mawardi And Its Relevance In Indonesia: The Study Of The Book Of Al-Ahkam As-Sulthaniyyah - Ahmad fauzan (Jurnal Penelitian, 2018)
This research is studying the character of leaders according to Imam Al-Mawardi in the Al-Ahkam As-Sulthaniyyah book and the relevance of al-Mawardi's thinking in the current Indonesian political context. The author focuses more on the concept of the appointment of a leader. This study uses a qualitative method with a Historical-Normative approach. The results of this study show that Al-Mawardi argued that enforcing government is a religious obligation. In the case of electing a leader, al-Mawardi provides specific criteria namely; (1) Fair; (2) Intellect; (3) Sensory health; (4) Healthy organs or not defective; (5) visionary or broad insight; (6) Brave, and (7) The Nasab comes from Quraysh. Most of the criteria qualified by al-Mawardi are still relevant if applied in Indonesia, especially in terms of the appointment of leaders. The concept of governance will be drawn in the legal framework (Islamic constitution) concerning the realization of public benefit in political decision making, so that answers will be obtained regarding the validity of the leadership character in the Islamic government system in the eyes of religious law and its relevance to the concept of leadership in Indonesia. Thus, the upright and prosperity of a region / country is very much determined by the quality of a leader. If a leader is someone who truly has leadership and has the criteria needed for a leader, it can be used as a measure and guarantee of the advancement of a country.